Inspiratory muscle training in pediatrics: main indications and technical characteristics of the protocols - Cristhiele Tais Woszezenki; João Paulo Heinzmann-Filho; Márcio Vinícius Fagundes Donadio
Abstract Introduction: Inspiratory muscle training (IMT) is a resource widely used in pediatrics. However, there is great variability in relation to the characteristics of the protocols used. Objective: To identify the main clinical conditions and IMT protocols used in the pediatric age group. Methods: Integrative review of the literature by searching on Pubmed, Scielo, PEDro and EMBASE databases using the following strategy: threshold OR inspiratory muscle training OR muscle endurance OR muscle resistance OR endurance training OR maximal inspiratory pressure AND respiratory muscle. We have selected clinical trials that performed IMT in children and adolescents (0 to 18 years old), with a clinical diagnosis, and published in English, Portuguese and Spanish. Results: 17 studies were included. From these, 11 underwent IMT in patients with some neuromuscular disorder, being Duchenne Muscular Dystrophy the most common. The selected articles included a total sample of 327 participants. As for the characteristics of the protocols, 7 performed strength training, 5 endurance and 5 strength and endurance. The training load ranged from 30 to 80% of maximal inspiratory pressure. Moreover, 8 studies performed IMT twice daily and the session duration and the training period varied between 10 and 30 minutes, and from 3 weeks to 24 months, respectively. Conclusion: The IMT was used more frequently in patients with some neuromuscular disorder. Although there is no consensus as to the characteristics of the protocols, the choice of the load should take into account the purpose of IMT and the disease severity.